Implementasi tata kelola perusahaan dalam mitigasi risiko manajemen kinerja pada perbankan syariah - Kurniawati, Lina (Maliki Interdisciplinary Journal, 2024)
Corporate governance (GCG) and risk management are two key aspects that influence sharia banking performance. GCG involves practices that ensure transparency, accountability and corporate sustainability. In sharia banking, GCG includes the existence of a Sharia Supervisory Board (DPS), internal and external sharia audits, as well as a sharia compliance unit. Good GCG implementation can help reduce financing risks and ensure the sustainability of Islamic banks. The aim of this research is to analyze the implementation of Corporate Governance (GCG) in mitigating performance management risks in sharia banking. The approach taken in this research is descriptive qualitative. This approach examines a group of people, objects, conditions, and contemporary systems of thought. The research results show that Islamic banks have implemented Good Corporate Governance (GCG) based on four principles: accountability, responsibility, justice and transparency. The implementation of GCG is in accordance with Bank Indonesia law. In addition, the sharia principles underlying sharia banking have been implemented effectively and implemented. Sharia is based on the characteristics of the prophet, such as shiddiq (honesty), amanah (trust), fathanah (intelligence), and tabligh (openness).